Structure‐based computational design of antibody mimetics: challenges and perspectives - Elton J. F. Chaves; Danilo F. Coêlho; Carlos H. B. Cruz; Emerson G. Moreira; Júlio C. M. Simões; Manassés J. Nascimento‐Filho; Roberto D. Lins (FEBS Open Bio)
The design of antibody mimetics holds great promise for revolutionizing therapeutic interventions by offering alternatives to conventional antibody therapies. Structure‐based computational approaches have emerged as indispensable tools in the rational design of those molecules, enabling the precise manipulation of their structural and functional properties. This review covers the main classes of designed antigen‐binding motifs, as well as alternative strategies to develop tailored ones. We discuss the intricacies of different computational protein–protein interaction design strategies, showcased by selected successful cases in the literature. Subsequently, we explore the latest advancements in the computational techniques including the integration of machine and deep learning methodologies into the design framework, which has led to an augmented design pipeline. Finally, we verse onto the current challenges that stand in the way between high‐throughput computer design of antibody mimetics and experimental realization, offering a forward‐looking perspective into the field and the promises it holds to biotechnology.